2003
DOI: 10.1034/j.1600-051x.2003.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐alpha gene (TNF‐α) −1031/−863, −857 single‐nucleotide polymorphisms (SNPs) are associated with severe adult periodontitis in Japanese

Abstract: Since the frequency of subjects who carried at least one variant allele in TNF-alpha-1031, -863 or -857 SNPs was higher in periodontitis patients than in healthy subjects, TNF-alpha-1031, -863 and -857 SNPs appear to be associated with severe adult periodontitis in Japanese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
138
2
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 38 publications
12
138
2
9
Order By: Relevance
“…An example of this is the role of the TNF-A-1031, -863 and -857 variants, which are observed in a relatively large proportion in Japanese populations and have a more marked influence on risk of several inflammatory conditions. 26 In summary, our study has confirmed that the proinflammatory IL-1B-31 genotypes contribute significantly to the risk of GC in a Hispanic population, mirroring the findings in Caucasians and Asians. This underscores the very important role that this cytokine plays in the pathogenesis of H. pylori-related gastric cancer.…”
Section: Il-1b-31(c/t) Tnf-a-308supporting
confidence: 83%
“…An example of this is the role of the TNF-A-1031, -863 and -857 variants, which are observed in a relatively large proportion in Japanese populations and have a more marked influence on risk of several inflammatory conditions. 26 In summary, our study has confirmed that the proinflammatory IL-1B-31 genotypes contribute significantly to the risk of GC in a Hispanic population, mirroring the findings in Caucasians and Asians. This underscores the very important role that this cytokine plays in the pathogenesis of H. pylori-related gastric cancer.…”
Section: Il-1b-31(c/t) Tnf-a-308supporting
confidence: 83%
“…One of them is transition replacement of adenine for guanine at positions -308 and the second polymorphism is transition replacement of thymine for cytosine at position -857. All PCR reactions were run under conditions previously described (Fargion et al, 2001;Soga et al, 2003). Primer sequences for the polymorphism at position -857(rs1799724) are sense 5′-AAG TCG AGT ATG GGG ACC CCC CGT TAA-3′ and anti-sense 5′-CCC CAG TGT GTG GCC ATA TCT TCT T-3′, those for the gene polymorphism at position -308 (rs361525) are forward 5′-GGG ACA CAC AAG CAT CAA GG-3′ and reverse 5′-GGG ACA CAC AAG CAT CAA GG-3′.…”
Section: Screening Of Tnf-α Promoter Polymorphisms By Pcr-restrictionmentioning
confidence: 99%
“…[8][9][10] Several functional promoter polymorphisms have been identified in this gene. [11][12][13][14][15] There is emerging evidence that of an association of TNF-α-308 polymorphism, a G/A transition at -308-bp position, which may alter promoter activity, with TNF-α expression in vitro, as well as plasma concentrations. 16 An increased serum concentration of TNF-α is an independent predictor of cardiovascular disease 17 and is a marker for recurrent coronary events following a previous acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%